Effect of austenite temperature and holding time to impact energy and wear on HRP steel - Yurianto, Yurianto; Suprihanto, Agus; Suryo, Sumar Hadi; Umardani, Yusuf; Yanuar, Padang (Eastern-European Journal of Enterprise Technologies, 2020)
Quenched and Tempered Steel is classified as high strength and hardness steel mostly used for armor steel. Hardness and wear stability is essential for steel armor quality standards. On the other hand, austenitization and tempering temperature affect the impact value of the energy absorbed and the Quenched and Tempered Steel wear resistance value. This study aims to evaluate the effects of austenitization and holding time on energy and hardness of Hot Rolled Plate Steel. The research material is a hot roller plate made by Krakatau Steel Indonesia Company Limited with a carbon content of about 0.29 %. The method used was heating of three specimens at 900 (held 45 minutes), 900 (held 30 minutes), and 900 (held 15 minutes), and all of them cooled into the water when the end of heating. Three specimens were heated at 885 (for 45 minutes), 885 (for 30 minutes), and 885 (for 15 minutes) and cooled into the water. Three specimens were heated at 870 (kept 45 minutes) 870 (held 30 minutes), and 870 (kept 15 minutes) and cooled into water. Then the final cooling of the nine specimens was heated at 150 for 30 minutes and cooled to the atmosphere. Five specimens tested for the hardness of Charpy and Vickers. Then arranged into an orthogonal matrix; calculate degrees of freedom; signal to noise ratio, quadratic parameters; average squared response; the ratio between the average response of the square of the source and the error; contribution parameters; predictive value and confidence interval. From the calculation above, the heat treatment parameters have a strong influence on the energy impact and the specific wear obtained. The most influential parameter on the energy impact is the tempering temperature because this parameter is softening caused by a reduction in residual stress due to the previous cooling process. The fine-grain structure increases strength and the energy impact directly